Potential of collagen‐like triple helical peptides as drug carriers: Their in vivo distribution, metabolism, and excretion profiles in rodents. Issue 6 (November 2013) - Yasui, Hiroyuki; Yamazaki, Chisato M.; Nose, Hiroshi; Awada, Chihiro; Takao, Toshifumi; Koide, Takaki; Gierasch, Lila; Lynn, David; Schneider, Joel
ABSTRACT Collagen‐model peptides composed of (X‐Y‐Gly)n sequences were used to study the triple helical structure of collagen. We report the stability of these collagen‐like peptides in biological fluids, and their pharmacokinetics including distribution, metabolism, and excretion in animals. A typical collagen‐model peptide, H‐(Pro‐Hyp‐Gly)10‐OH, was found to be extremely stable in the plasma and distributed mainly in the vascular blood space, and was eliminated through glomerular filtration in the kidneys. Triple helical peptides of (X‐Y‐Gly)n sequences were quantitatively recovered from the urine of rats after intravenous injection regardless of the differences in peptide net charge between −3 and +6 per triple helix. In contrast, the renal clearance became less efficient when the number of triplet repeats (n) was 12 or more. We also demonstrated the application of a collagen‐like triple helical peptide as a novel drug carrier in the blood with a high urinary excretion profile. We further demonstrated that a collagen‐like triple helical peptide conjugated to a spin probe, PROXYL, has the potential to evaluate the redox status of oxidative stress‐induced animals in vivo. © 2013 Wiley Periodicals, Inc. Biopolymers (Pept Sci) 100: 705–713, 2013.